Changing Trends in Therapeutic Plasmapheresis: An Indian Perspective. Issue 5 (11th September 2017) - Tiwari, Aseem K; Bhardwaj, Gunjan; Aggarwal, Geet; Arora, Dinesh; Dara, Ravi C; Acharya, Devi P; Gayam, Sangeetha; Choudhuri, Jui
Abstract: Indications for therapeutic apheresis (TA) are dynamic; they keep changing and expanding because of introduction of newer treatment modalities and accumulating evidence in the form of case‐reports, case‐series and original articles. We evaluated our therapeutic plasmapheresis (TP) data and compared this data with an earlier published Indian report for indications, frequency, response rate and adverse reactions. We conducted a retrospective analysis of all TP procedures performed from January 2014 to June 2016 in department of Transfusion Medicine at a tertiary care hospital. All TP procedures performed for various clinical disorders including neurological, hematological, renal, hepatic and rheumatologic indications were included in the study. Analysis was performed with respect to demography, procedure details and response. 187 patients (118 Males and 69 females) underwent 683 TP procedures during study period. According to 2013 ASFA guidelines, 99, 59 and 29 patients belonged to category I, II and III respectively. In comparison with the earlier report, the number of patients and procedures have increased, indications have changed, response rate is comparable, and the frequency of adverse reactions have decreased. In the last decade there has been increase in number and spectrum of indications for therapeutic apheresis and frequency of procedures. The response rate and safety of these procedures have also improved.